2005
DOI: 10.1158/0008-5472.can-04-4141
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Thioredoxin as a Molecular Target for Antitumor Quinols

Abstract: Heteroaromatic quinols 4-(benzothiazol-2-yl)-4-hydroxycyclohexa-2,5-dienone (1) and 4-(1-benzenesulfonyl-1H-indol-2-yl)-4-hydroxycyclohexa-2,5-dienone (2) exhibit potent and selective antitumor activity against colon, renal, and breast carcinoma cell lines in vitro (GI 50 < 500 nmol/L). In vivo growth inhibition of renal, colon, and breast xenografts has been observed. Profound G 2 -M cell cycle block accompanied down-regulation of cdk1 gene transcription was corroborated by decreased CDK1 protein expression f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 21 publications
(25 reference statements)
5
85
2
Order By: Relevance
“…Indeed, compounds that interact with Trx do not necessarily react with Tpx. The antitumor benzothiazole-substituted quinole PMX464 inhibits Trx (21)(22)(23). A recent study on the T. brucei peroxidase system revealed that the quinole reacts with T(SH) 2 as well as Px and Prx but not with Tpx or TR (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, compounds that interact with Trx do not necessarily react with Tpx. The antitumor benzothiazole-substituted quinole PMX464 inhibits Trx (21)(22)(23). A recent study on the T. brucei peroxidase system revealed that the quinole reacts with T(SH) 2 as well as Px and Prx but not with Tpx or TR (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently the effect of the antitumor quinol PMX 464 on the parasite peroxidase systems has been studied (20). In mammalian and yeast cells, the quinol inhibits thioredoxin (21)(22)(23). Toward T. brucei, PMX 464 showed cytocidal activity and caused depletion of cellular T(SH) 2 .…”
mentioning
confidence: 99%
“…AW464 is a benzothiazole-substituted quinol compound that has been shown by mass spectrometry to bind to Trx-1 and has been proposed to cross-link irreversibly to cysteine residues 32 and 35 of Trx-1 active site via its two h-carbon atoms; the first link is reversible, whereas the second cross-link is thought to be irreversible (36,41). AW464 can inhibit VEGF expression in hypoxic colorectal cells, and hypoxia has been shown to sensitize colorectal cancer cells to antiproliferative effect of AW464 (35).…”
Section: Discussionmentioning
confidence: 99%
“…AW464 can inhibit VEGF expression in hypoxic colorectal cells, and hypoxia has been shown to sensitize colorectal cancer cells to antiproliferative effect of AW464 (35). Further chemical syntheses and structure activity screening uncovered AJM290, an indole-substituted quinol that possess enhanced potency in vitro against human derived colon, renal, and mammary carcinoma cell lines and in vivo antitumor activity against breast, colon, and renal mouse xenografts (36,42).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Hydroxycyclohexadienone analogues, of which PMX464 is the parent compound, have encouraging results in inhibitory trials against Mtb H 37 Rv strains in vitro 17 and studies showed that MtbTrxC catalyzed reduction of insulin is inhibited by PMX464 in a potent and dose-dependent manner consistent with irreversible inhibition of Trx (IC 50 < 6 lM). 18 To investigate how the inhibitor binds and thus provide a template for design and development we have determined the structure of PMX464 in complex with a catalytically inactive MtbTrxC.…”
Section: Introductionmentioning
confidence: 99%